2019
DOI: 10.1111/een.12825
|View full text |Cite
|
Sign up to set email alerts
|

Multitrophic interactions drive body size variations in seed‐feeding insects

Abstract: 1. The intensity of community interactions and the structure of food webs can be associated with an organism's body size. However, little is known about how interactions among species in multitrophic communities determine the body size of individuals exploiting the same resource.2. This study evaluates the effects of resource size, fruit infestation, and parasitism on tibia length, a proxy measure of body size, of insects exploiting the same resource. The three most abundant seed-feeding species of Senegalia t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 50 publications
1
10
1
Order By: Relevance
“…Furthermore, we were unable to observe the effect of the infestation and parasitism rate on the allometry of the structures of S. maculatopygus, as they were absent in the medium and high categories, showing somehow their low tolerance to stresses caused by fruit infestation and parasitism, something already suggested in other studies [23,33,35]. Besides, the values of the elytra and pronotum allometry of S. maculatopygus were close to zero, indicating that the allometry of S. maculatopygus is not a very sensitive parameter to changes in the amount of the resource, which can be reinforced by the results of other studies, in which the body size of S. maculatopygus was not related to the size of the resource [23,35].…”
Section: Plos Onecontrasting
confidence: 56%
See 2 more Smart Citations
“…Furthermore, we were unable to observe the effect of the infestation and parasitism rate on the allometry of the structures of S. maculatopygus, as they were absent in the medium and high categories, showing somehow their low tolerance to stresses caused by fruit infestation and parasitism, something already suggested in other studies [23,33,35]. Besides, the values of the elytra and pronotum allometry of S. maculatopygus were close to zero, indicating that the allometry of S. maculatopygus is not a very sensitive parameter to changes in the amount of the resource, which can be reinforced by the results of other studies, in which the body size of S. maculatopygus was not related to the size of the resource [23,35].…”
Section: Plos Onecontrasting
confidence: 56%
“…The structure measurements in the two coleopteran species were pronotum width, and both left and right elytra length and width [20,23] (Fig 2A and 2B). For the hymenopteran species A. vulgaris, we measured total body size length (thorax + abdomen) [43,49,50], +R vein until the end of 3RSb vein, wing width measured from the junction between anterior wing length measured from the beginning of C+Sc, the parastigma and stigma to the end of vein 1A ( Fig 2C) (adapted from [44]); and posterior tibia length was measured from the junction of the femur and the tibia to the junction of the tibia and tarsus [23,35]. Wings and tibia from the https://doi.org/10.1371/journal.pone.0241913.g001…”
Section: Morphological Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this result may reflect the habit of this species to feed on the ends of the seed, allowing the exploitation of the resource by more than one individual [78]. In addition to this, we observed in the laboratory that the seeds preyed upon by these individuals are almost completely consumed, which would explain this negative relationship between the seed biomass and the body size of A. vulgaris [35].…”
Section: Plos Onementioning
confidence: 77%
“…Nevertheless, most studies have analyzed isolated factors influencing the body size of organisms [23,[27][28][29][30][31][32][33] and few considered multiple interactions affecting body size at the same time [34,35]. Recently, we observed that interactions in a multi-trophic network can drive to changes in the body size of seed-feeding insects differently, in which abundant species have their body size more affected than less abundant ones [35]. Likewise, although there are several studies considering isolated factors influencing morphometric patterns (e.g.…”
Section: Introductionmentioning
confidence: 99%